Desarrollo de competencias ciudadanas fundamentadas en la promoción de la identidad afrocolombiana y la diversidad étnica (2024)
The present work aims to contribute to generating the basis for a change of thought in the academic population and reflecting it in citizens who contribute to building a better society. Therefore, the objective is to design a pedagogical proposal that, based on the curricular integration of Afro-Colombian identity and ethnic diversity, contributes to the development of citizenship competencies in primary school students. The study is contextualized in the IED Mundo Bolivariano and La Esmeralda, located in the Las Malvinas and La Esmeralda neighborhood in the southwest locality of the Barranquilla district, Atlántico, Colombia. The epistemological component is based on a rational logical approach under a critical rationalist paradigm through a documentary and field design. In the documentary stage, the units of analysis are represented by the PEI, where a triangulation is carried out comparing the discoveries presented in the document by its authors, contrasting them with the theory and the argumentative position adopted by the researchers. Among the main results, it is highlighted that the implementation of interactive and participatory activities in the project has allowed children to appreciate the different cultural manifestations present in the region, promoting respect, empathy, and understanding towards ethnic and cultural diversity. The research concludes that it has provided a solid foundation for the development of project activities, enriching the understanding and appreciation of the region's cultural richness